2008
DOI: 10.1007/s10544-008-9163-x
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification of a single DNA molecule in polyacrylamide gel-based microchamber

Abstract: Loop-mediated isothermal amplification (LAMP) is an original nucleic acid amplification method established by Notomi et al. LAMP is performed under isothermal condition, employing only a basic reaction protocol and minimal supporting electronics. These requirements prove to be viable for exploring the avenues to down-scale this biological reaction for Lab-on-a-chip application. Hence here, we developed a novel technique for fluorescent imaging of LAMP at a single molecule level. The experiment was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 20 publications
(13 reference statements)
0
33
0
Order By: Relevance
“…polymethyl methacrylate (PMMA) or polydimethylsiloxane (PDMS)) reported previously. This consideration would be more important where the fabrication of microfluidic systems need some biocompatible polymers such as PMMA, PDMS or polyacrylic acid (PAA) [32][33][34]. Fabrications of polymeric microfluidics encountered with some problems such as preparation of the polymer molding solution, multilayer polymers, and penetration of the reaction mixtures in a polymer-based platform.…”
Section: Discussionmentioning
confidence: 99%
“…polymethyl methacrylate (PMMA) or polydimethylsiloxane (PDMS)) reported previously. This consideration would be more important where the fabrication of microfluidic systems need some biocompatible polymers such as PMMA, PDMS or polyacrylic acid (PAA) [32][33][34]. Fabrications of polymeric microfluidics encountered with some problems such as preparation of the polymer molding solution, multilayer polymers, and penetration of the reaction mixtures in a polymer-based platform.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these characteristics both dyes are ideal candidates for end point detection of the LAMP (Soheili & Samiei 2005;Zipper et al 2004). Previous studies had reported the inhibitory effect of SYBR Green I on quantitative real-time LAMP (Lam et al 2008). Therefore, in this study, SYBR Green I and SYBR Safe dyes were added after the amplification was completed which resulted in the shorter threshold time, Tt (12 mins) (Figures 3 & 4).…”
Section: Discussionmentioning
confidence: 93%
“…While lower copy numbers were not evaluated, it is anticipated that a sensitivity of a few copies per well should be achievable using the LAMP microfluidic chip. This is because: i) detection of single copies has been reported previously using LAMP in conventional tubes (Thekisoe et al 2010;Tsai et al 2009;Yamazaki et al 2008b) and also in microscale systems based on endpoint fluorescence detection (Lam et al 2008;Gansen et al 2012), and ii) we routinely observed that amplification efficiency of LAMP in chips fabricated out of untreated polymeric substrates (COP and polyester), is similar to that in tubes Stedtfeld et al 2012). As such, the microfluidic chip is expected to provide a sensitivity that is comparable to that of most molecular assays, including PCR, but with the added benefit of multiplexed detection in an inexpensive and easy-to-use format.…”
Section: Parallel Detection Of Multiple Pathogensmentioning
confidence: 92%